Peran Guru dalam Mengembangkan Kesadaran Diri Anak Usia Dini - Miyani, Rizki; Zulkarnain, Ali Iskandar; Saudah, Saudah (Paedagogie, 2026)
This study aims to describe the role of teachers as motivators, guides, and facilitators in developing children's self-awareness, as well as to portray the condition of self-awareness among early childhood students at RA Annisa 2 Palangka Raya. The background of this study is based on initial observations indicating that some children had not demonstrated independence in choosing activities, had difficulty controlling emotions, lacked self-confidence, had not consistently followed rules and discipline, showed little persistence, and lacked pride in their own abilities. This study employed a descriptive qualitative approach. Research informants consisted of one Class A teacher, the school principal, and 18 Class A children. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with source triangulation and technique triangulation applied to ensure data validity. The findings indicate that teachers carried out their roles in three forms: (1) as a motivator, by providing praise, star rewards, and verbal reinforcement; (2) as a guide, by offering direct instruction and persuasive guidance to children experiencing difficulties; and (3) as a facilitator, by providing varied learning media such as emotion cards and rule boards, and by creating a safe and conducive classroom environment. Children's self-awareness development was observed across aspects of independent activity selection, emotional regulation, self-confidence, adherence to rules and discipline, persistence, and pride in their own work. These findings suggest that the active integration of teacher roles is closely associated with the development of self-awareness as a foundation for children's social-emotional intelligence.